The Malaysian IPO Market: Volume, Initial Returns and Economic Conditions - Chong, Fennee; Puah, Chin Hong (Zant World Press, Australia, 2009)
This paper analyses the time series behaviour of the IPO volume, initial returns and economic conditions of the Malaysian IPO market. The ARDL bounds testing approach was used to examine these variables. Empirical results showed that both initial returns and economic conditions have significant long-run relationships with IPO volume. Furthermore, these two variables are also found to Granger- cause the IPO volume in the short-run.